An Improved Method to Shorten Physiological Dormancy of Giant Ragweed (Ambrosia trifida) Seed. Issue 2 (9th January 2019) - Harre, Nick T.; Weller, Stephen C.; Young, Bryan G.
Abstract: Timely results from whole-plant, herbicide-resistant weed screenings are crucial to heighten grower awareness. However, the high degree of physiological dormancy of giant ragweed ( Ambrosia trifida L.) seed exacerbates this process. The most effective methods for alleviating dormancy, to date, are either labor-intensive (embryo excision) or require several weeks (soil stratification). This research describes a conditioning process involving clipping and aeration of seed in water that is highly effective at alleviating dormancy and requires less skill and time compared with previous techniques. Ambrosia trifida seeds were collected over 2 yr at two different collection timings (September 25, "early"; October 25, "late"), subjected to various treatments intended to release dormancy, and evaluated for emergence over 18 d in the greenhouse. The use of germination-promoting chemicals (ethephon, gibberellic acid, and thiourea) generally provided no increase in emergence compared with water and occasionally produced seedlings with abnormal growth unsuitable for further experimentation. Conditioning yielded between 30% and 33% emergence for both early and late collections of seeds with no afterripening period compared with 0% emergence for seeds imbibed in water. Following an 8-wk period of dry storage at 4 C, conditioning yielded nearly 80% emergence for both collection timings, while emergence of seeds imbibed in water was 10% and 27% for early and late collections, respectively. Soil stratification in moist soil for 8 wk at 4 C was the second most effective treatment, yielding 46% to 49% emergence across both collections. Parameters of the Weibull function further indicated the conditioning treatment had the fastest rate of emergence and shortest lag phase between planting and first emergence. Methods to germinate A. trifida without an afterripening period have previously been unsuccessful. Therefore, the seed-conditioning method outlined in this work will be useful in expediting the confirmation of herbicide-resistant A. trifida incidences.